2013
DOI: 10.1063/1.4846575
|View full text |Cite
|
Sign up to set email alerts
|

Vibrationally induced center reconfiguration in co-doped GaN:Eu, Mg epitaxial layers: Local hydrogen migration vs. activation of non-radiative channels

Abstract: Europium doped gallium nitride (GaN:Eu) is a promising candidate as a material for red light emitting diodes. When Mg was co-doped into GaN:Eu, additional incorporation environments were discovered that show high excitation efficiency at room temperature and have been attributed to the coupling of Mg-H complexes to the majority Eu site. Electron beam irradiation, indirect and resonant (direct) laser excitation were found to modify these complexes, indicating that vibrational energy alone can trigger the migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…It is important to mention at this point that two other models from the literature2021 purport to explain temperature dependent switching of Eu-Mg defects; both of these models are incomplete in the sense that the authors have not recorded PL spectra during both a cooling and a warming run, which is essential to observe the hysteretic photochromic switching and necessary to describe its mechanism. In the first model, Lee et al 20.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to mention at this point that two other models from the literature2021 purport to explain temperature dependent switching of Eu-Mg defects; both of these models are incomplete in the sense that the authors have not recorded PL spectra during both a cooling and a warming run, which is essential to observe the hysteretic photochromic switching and necessary to describe its mechanism. In the first model, Lee et al 20.…”
Section: Discussionmentioning
confidence: 99%
“…They describe the decrease in Eu1(Mg) (their peak B) PL intensity with increasing temperature as a typical temperature dependent PL behaviour of GaN:Eu and propose that the increase in PL intensity of Eu0 (peak A), up to 180 K, during warming, might be due to an increase in energy transfer efficiency from the host to the Eu0 defect. In the second model, Mitchell et al 21. propose that Eu0 (their Mg/Eu1) defect results from a coupling of a magnesium hydrogen (Mg-H) complex with Eu in GaN(Mg):Eu, and that under indirect or resonant excitation below 60 K, vibrational energy triggers H migration and modifies the complex which results in a transformation of the spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of this displacement depends on the charge state of the complex. A similar observation was made on Mg-H-Eu complexes in GaN:Eu that was co-doped with Mg. [20,21] In these samples, a new Mg-H related center was observed that had a significantly blue shifted emission spectra, relative to the standard Eu emission peaks. Thus, the appearance of emission peaks that differ from each other should be expected as signature of defect complexes of different charge states.…”
Section: A Dft+u Calculations Of V Ga -Eu Complexes With Different Cmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The magnetic properties of GaN:Eu and other rare earth doped GaN dilute magnetic semiconductor (DMS) systems have also been extensively investigated for spintronic applications. [9][10][11][12][13][14][15] It is known that the Eu ions will incorporate into GaN in several defect environments, and that these defect environments play an important role on the spectral position of the Eu emission, [16][17][18][19][20][21][22][23][24] and in the ability for the Eu ions to capture energy from the GaN host during the recombination of electrons and holes. [7,18,22] Extensive spectroscopic work has provided ample evidence that the two main emitting centers, referred to as Eu1 and Eu2, are complexes consisting of a Eu ion on gallium site with either a nitrogen (V N ) or (V Ga ) gallium vacancy in close proximity.…”
Section: Introductionmentioning
confidence: 99%